TL1A/DR3 Axis, A Key Target of TNF-a, Augments the Epithelial–Mesenchymal Transformation of Epithelial Cells in OVA-Induced Asthma - Zhang, Dong; Yang, Hui; Dong, Xue-Li; Zhang, Jin-Tao; Liu, Xiao-Fei; Pan, Yun; Zhang, Jian; Xu, Jia-Wei; Wang, Zi-Han; Cui, Wen-Jing; Dong, Liang (Frontiers in Immunology, 2022)
Tumor necrosis factor (TNF)-like cytokine 1A (TL1A), a member of the TNF family, exists in the form of membrane-bound (mTL1A) and soluble protein (sTL1A). TL1A binding its only known functional receptor death domain receptor 3 (DR3) affects the transmission of various signals. This study first proposed that the TL1A/DR3 axis was significantly upregulated in patients and mice with both asthma and high TNF-a expression and in TNF-a-stimulated epithelial Beas-2B cells. Two independent approaches were used to demonstrate that the TL1A/DR3 axis of mice was strongly correlated with TNF-a in terms of exacerbating asthmatic epithelial–mesenchymal transformation (EMT). First, high expression levels of EMT proteins (e.g., collagen I, fibronectin, N-cadherin, and vimentin) and TL1A/DR3 axis were observed when mice airways were stimulated by recombinant mouse TNF-a protein. Moreover, EMT protein and TL1A/DR3 axis expression synchronously decreased after mice with OVA-induced asthma were treated with infliximab by neutralizing TNF-a activity. Furthermore, the OVA-induced EMT of asthmatic mice was remarkably improved upon the deletion of the TL1A/DR3 axis by knocking out the TL1A gene. TL1A siRNA remarkably intervened EMT formation induced by TNF-a in the Beas-2B cells. In addition, EMT was induced by the addition of high concentrations of recombinant human sTL1A with the cell medium. The TL1A overexpression via pc-mTL1A in vitro remarkably increased the EMT formation induced by TNF-a. Overall, these findings indicate that the TL1A/DR3 axis may have a therapeutic role for asthmatic with high TNF-a level.